Corporate social responsibility, trade credit and financial crisis - Asif Saeed; Qasim Zureigat (Journal of Risk and Financial Management, 2020)
Socially responsible firms receive more finance and have been well researched in the corporate finance literature. In this paper, we examine the relationship between CSR and trade credit. Using data from the US manufacturing industry, we find that CSR has a significant positive association with the buyer and supplier sides of trade credit. During the 2008–2009 financial crisis, the manufacturing industry trade badly fell. We also argue and find evidence that, during crisis, CSR is negatively associated with trade credit. These findings are robust for alternate proxies of CSR and trade credit, sample selection, and time period. Moreover, the potential endogeneity concerns do not affect our results. Finally, we show that this relationship exists for both domestic and multinational firms' subsamples. Overall, our results indicate that firms with high social performance use more trade credit to increase their business activity.
Keywords: 330; corporate social responsibility; crisis; multinationals; trade credit